2014
DOI: 10.1038/oncsis.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sonic hedgehog signaling in neural progenitor cells promotes glioma development in the zebrafish optic pathway

Abstract: Dysregulation of Sonic hedgehog (Shh) signaling has been implicated in glioma pathogenesis. Yet, the role of this pathway in gliomagenesis remains controversial because of the lack of relevant animal models. Using the cytokeratin 5 promoter, we ectopically expressed a constitutively active zebrafish Smoothened (Smoa1) in neural progenitor cells and analyzed tumorigenic capacity of activated Shh signaling in both transient and stable transgenic fish. Transient transgenic fish overexpressing Smoa1 developed reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Several recent studies demonstrated the role of sonic hedgehog signaling, specifically GLI1 in glioblastoma progression and the role of GLI1 in imparting stem cells characteristics [2]. Interestingly, GLI1 was found to be up-regulated in glioblastoma and responsible for chemo-resistance [9, 10]. We observed that penfluridol treatment reduced the expression of GLI1 in all the glioblastoma cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 53%
“…Several recent studies demonstrated the role of sonic hedgehog signaling, specifically GLI1 in glioblastoma progression and the role of GLI1 in imparting stem cells characteristics [2]. Interestingly, GLI1 was found to be up-regulated in glioblastoma and responsible for chemo-resistance [9, 10]. We observed that penfluridol treatment reduced the expression of GLI1 in all the glioblastoma cells in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 53%
“…Once SHH binds to its receptor Patched 1, the transmembrane protein Smoothened is released, causing the transport of the transcription factor glioma-associated oncogene (Gli) into the nucleus, where it regulates the transcription of target genes that control cell differentiation, survival and growth (5,6). Three Gli genes (Gli1, Gli2 and Gli3) have been identified in mammalian tissues, among which Gli1 is considered to be the only loyal marker of hedgehog pathway activity (8)(9)(10) studies have shown that the hedgehog pathway is associated with the migration and invasion of ovarian, pancreatic, esophageal and gastric carcinomas (6,(11)(12)(13). However, to date, the implication of the hedgehog pathway in the aggressiveness of GBM has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ju and colleagues demonstrated that constitutively active smoothened is oncogenic in zebrafish and that co-expression with the human constitutively active Akt leads to glioblastoma-like tumors in the brain, retina and spinal cord (Ju et al, 2009). Recently, they also reported that Shh activation in neural progenitor cells prone the development of optic pathway glioma in the zebrafish (Ju et al, 2014). Beneath the fact that zebrafish can develop almost any kind of tumor it was shown that the zebrafish is suited as xenograft model for multiple human cancer cell lines.…”
Section: Accepted Manuscriptmentioning
confidence: 99%